Run from fear - Alden, Jami (New York : Forever, 2012)
Talia Vega wanted to leave behind her harrowing past. Moving 800 miles away, she succeeded--until the one man who knows her darkest secrets wanders into the restaurant where she works. Now the agonizing memories come crashing back--along with an undeniable desire for Jack Brooks, the ex-Green Beret who rescued her from a sadistic monster two years ago